Effect of chronotype on motor skills specific to soccer in adolescent players. (2nd April 2020) - Roveda, E.; Mulè, A.; Galasso, L.; Castelli, L.; Scurati, R.; Michielon, G.; Esposito, F.; Caumo, A.; Montaruli, A.
ABSTRACT: Circadian rhythms influence daily behavior, psychological and physiological functions, as well as physical performance. Three chronotypes are distinguished according to the preferences people typically display for activity at certain times of day: Morning, Neither, and Evening types (M-, N- and E-types). The chronotype changes with age: eveningness tends to be stronger in youth and morningness in older age. The progressive shift toward eveningness during adolescence creates misalignment with morning society schedules and can lead to a deterioration in intellectual and physical performance. Soccer is one of the world's most popular sports practiced by adolescents and soccer workouts are usually held after school in the afternoon or evening. Performance in soccer is related to a host of factors, including physiological variables and motor skills that have a circadian variation. The aim of this study was to determine the effect of chronotype on motor skills specific to soccer, specifically whether agility, aerobic endurance, and explosive power differ among the three chronotypes in relation to the time of day. For this study 141 adolescent soccer players filled in the Morningness-Eveningness Questionnaire (MEQ) for the assessment of chronotype. A subsample of 75 subjects, subdivided in M-types (n= 25), E-types (n= 25), and N-types (n= 25), performed three tests (Sargent Jump Test - SJT, Illinois Agility Test - IAT, and 6-Minutes Run Test - 6MRT) at a morning and an evening training session (9:00 am and 6:00 pm). Mixed ANOVA was used to test the interactions between chronotypes, physical performance, and time. On all tests, better performance during the morning than the evening session was observed for the M-types ( p < .05), whereas the E-types performed better in the evening than in the morning session ( p < .05),  and no differences in test performance were detected for the N-types. These findings underline the importance of a correct chronobiological approach to sports training. Scheduling training sessions according to an athlete's circadian preferences could be a valid strategy to enhance performance.